Graduate trainees’ perceptions of their psychological contract: A case study - Shanya Reuben; Shaida Bobat; Celukuthula Makhoba (SA Journal of Industrial Psychology)
Orientation: In response to South Africa’s historical context and persistent social and economic challenges, many organisations recognise the importance of graduate programmes as instruments for cultivating technical and behavioural competencies to facilitate business development and sustainability. We assert that the psychological contract (PC) should be highlighted as a crucial foundation for promoting workplace success for both graduates and employers.